Relationship between anxiety and hyperemesis gravidarum in pregnant women from Trujillo, Peru: A prospective cohort study - Jackelin Pricila Cusi-Ortiz de Orué; Johnny Fernando Quiñones-Jauregui; Maria Dolores Mondejár-Barrios (TUMI Health Sciences Research, 2026)
Background: Hyperemesis gravidarum (HG) is a severe pregnancy-related condition that may substantially affect maternal physical and psychological well-being. Anxiety frequently coexists with HG, although evidence regarding whether anxiety precedes its occurrence remains limited, particularly in Peruvian populations. Objective: To evaluate the association between anxiety and HG among pregnant women in Trujillo, Peru. Methods: A prospective cohort study was conducted among 216 pregnant women receiving antenatal care at public healthcare facilities in Trujillo, Peru, between August and September 2025. Anxiety was assessed at enrollment using the validated Spanish version of the 20-item Zung Self-Rating Anxiety Scale, with scores ≥45 indicating anxiety. Women with HG diagnosed at enrollment were excluded, and participants were subsequently followed for incident HG through 20 weeks of gestation. HG was identified from physician-recorded diagnoses supported by persistent nausea and vomiting with clinically relevant features. Crude risk ratios (RRs) and adjusted odds ratios (aORs) with 95% confidence intervals (CIs) were estimated. Results: HG occurred in 56 of 108 women with anxiety (51.9%) and 20 of 108 women without anxiety (18.5%). Anxiety was associated with a higher crude risk of HG (RR, 2.80; 95% CI, 1.81–4.33; p < 0.001) and remained significantly associated after multivariable adjustment (aOR, 5.51; 95% CI, 2.66–11.38; p < 0.001). Conclusions: Anxiety was associated with a higher occurrence of HG in this prospective cohort. These findings support consideration of anxiety assessment as part of comprehensive antenatal care; however, they do not establish a causal relationship.